2017
DOI: 10.3389/fnmol.2017.00401
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CIB2 Causes Profound Hearing Loss and Abolishes Mechanoelectrical Transduction in Mice

Abstract: Calcium and integrin-binding protein 2 (CIB2) belongs to a protein family with four known members, CIB1 through CIB4, which are characterized by multiple calcium-binding EF-hand domains. Among the family members, the Cib1 and Cib2 genes are expressed in mouse cochlear hair cells, and mutations in the human CIB2 gene have been associated with nonsyndromic deafness DFNB48 and syndromic deafness USH1J. To further explore the function of CIB1 and CIB2 in hearing, we established Cib1 and Cib2 knockout mice using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 58 publications
2
86
0
Order By: Relevance
“…Considering the early expression of Rbm24 in ear placodes in chick and mouse embryos depicted in Figure and due to our great interest in identifying the molecular mechanisms involved in hair cells mediated hearing mechanoelectrical transduction, we examined the expression of Rbm24 in inner ear of neonate mice (Xu et al, ; Wang et al, ). Moreover, a nice study has recently demonstrated using RNA‐seq and ChIP‐seq experiments performed on purified cochlear cells at E17.5, that Rbm24 is a direct target gene of transcription factor Atoh1 and that it is thus activated in inner and outer hair cells in mice (Cai et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the early expression of Rbm24 in ear placodes in chick and mouse embryos depicted in Figure and due to our great interest in identifying the molecular mechanisms involved in hair cells mediated hearing mechanoelectrical transduction, we examined the expression of Rbm24 in inner ear of neonate mice (Xu et al, ; Wang et al, ). Moreover, a nice study has recently demonstrated using RNA‐seq and ChIP‐seq experiments performed on purified cochlear cells at E17.5, that Rbm24 is a direct target gene of transcription factor Atoh1 and that it is thus activated in inner and outer hair cells in mice (Cai et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the early expression of Rbm24 in ear placodes in chick and mouse embryos depicted in Figure 1 and due to our great interest in identifying the molecular mechanisms involved in hair cells mediated hearing mechanoelectrical transduction, we examined the expression of Rbm24 in inner ear of neonate mice (Xu et al, 2008;Wang et al, 2017). Moreover, a nice study has recently demonstrated using RNA-seq and ChIP-seq Figure 2.…”
Section: Rbm24 Is Expressed In Inner Ear Sensory Epithelia Cellsmentioning
confidence: 99%
“…For instance, CIB2 is down-regulated in ovarian cancer and associated with poor prognosis in ovarian cancer patients 36 . Previously, we and others reported on the essential function of CIB2 in the inner ear development and mechanotransduction of sound signal 16,37,38 . Furthermore, Cib2 deficient mice showed small, but not statistically significant difference in ERG amplitude between heterozygous and homozygous mice, leading the authors to conclude that CIB2-deficient mice exhibit no retinal phenotype 37 .…”
Section: Discussionmentioning
confidence: 90%
“…These are transmembrane channel-like proteins 1 and 2 (TMC1 and TMC2; Pan et al, 2013 ; Maeda et al, 2014 ; Kurima et al, 2015 ), tetraspan membrane protein in hair cell stereocilia (TMHS; also known as Lipoma HMGIC Fusion Partner-Like 5; LHFPL5; Xiong et al, 2012 ; Mahendrasingam et al, 2017 ), and transmembrane inner ear expressed gene (TMIE; Zhao et al, 2014 ; Figure 3A , Table 1 ). Other proteins such as CIB2 and TOMT are also essential for mechanotransduction (Riazuddin et al, 2012 ; Cunningham et al, 2017 ; Erickson et al, 2017 ; Giese et al, 2017 ; Michel et al, 2017 ; Wang et al, 2017 ) but will not be considered here because they do not encode proteins with multiple transmembrane domains and therefore are not predicted to be components contributing to the pore of the mechanotransduction channel. TMC1 and TMC2 have been proposed to be the pore-forming components of the mechanosensory channels (Corey and Holt, 2016 ), but direct evidence for this hypothesis is still lacking (Wu and Müller, 2016 ) and the role of LHFPL5 and TMIE in the channel complex still needs to be determined.…”
Section: Molecular Composition Of Mechanotransdution Channels In Hairmentioning
confidence: 99%